2013
DOI: 10.1007/s13139-013-0258-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of 68Ga-DOTATATE PET/CT in Liver Metastases of Neuroendocrine Tumours of Unknown Origin

Abstract: Our small study indicates that (68)Ga-DOTATATE PET/CT is a promising diagnostic option in the multimodality approach to neuroendocrine liver metastases of unknown primary origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…68 Ga-DOTATATE PET/CT has proven to be a pertinent tool in management of NETs, its utility extending right from diagnosis until prognostication of the disease (9)(10)(11)(12). Another important role that 68 Ga-DOTATATE PET/ CT can play is the detection of the primary tumor site in patients of CUP-NETs, an essential step toward patient management (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Ga-DOTATATE PET/CT has proven to be a pertinent tool in management of NETs, its utility extending right from diagnosis until prognostication of the disease (9)(10)(11)(12). Another important role that 68 Ga-DOTATATE PET/ CT can play is the detection of the primary tumor site in patients of CUP-NETs, an essential step toward patient management (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-DOTATATE PET/CT has proven to be superior to conventional imaging modalities in detecting the primary in patients with CUP-NET (15)(16)(17)(18)(19)(20). All the cases of CUP-NET are usually initially worked up with conventional imaging modalities such as ultrasonography, CT/ceCT, MRI, and EUS where applicable, which are unsuccessful in identifying the site of origin.…”
Section: Discussionmentioning
confidence: 99%
“…These include immunohistochemistry of transcription factors (CDX-2, Islet-1, TTF-1) [88], PET/CT (e.g. Ga 68-SR, 11 C-5-hydroxytryptophan or 18 F-DOPA) [89,90] and upper and lower gastrointestinal endoscopy and optionally capsule endoscopy [91,92]. If the primary tumor site remains unknown, therapeutic decision making is essentially based on grading, functionality, SSTR status, tumor extent and hepatic tumor burden.…”
Section: Management Of Net With Unknown Primary Tumormentioning
confidence: 99%
“…Enteroscopy has low accuracy in detecting NETs of the small intestine (sensitivity of 33%) [ 39 ]. As for functional tests, PET/CT 68 Ga is considered an excellent imaging method for detecting occult primary tumours [ 40 43 ]. An observational study showed that PET/CT 68 Ga identified 59% of occult NETs [ 41 ].…”
Section: Diagnosis and Stagingmentioning
confidence: 99%